Peningkatan pemahaman hukum bagi masyarakat dalam pengendalian kebakaran hutan dan lahan di Desa Petapahan Kecamatan Tapung Kabupaten Kampar - Syaifullah Yophi Ardiyanto; Setia Putra; Tengku Arif Hidayat; Muhammad A. Rauf; Samariadi Samariadi (Unri Conference Series: Community Engagement, 2020)
Riau Province is one of the provinces in Indonesia with the problem of forest and land fires that always occur every year. There is a need for understanding and participation from various parties, not only the government but also the community in controlling land forest fires so that land forest fires no longer occur in Riau Province according to Presidential Instruction No.3 of 2020 concerning Forest and Land Fire Management. Therefore, there is a need for activities to increase the role and understanding of the law for the community in controlling forest and land fires in Riau Province, especially in Petapahan Village, Tapung District, Kampar Regency. The service method is carried out using the waterfall model with eight stages of activity: (1) Problem Analysis; (2) Problem Identification; (3) Problem Formulation; (4) Development of Alternative Solutions; (5) Selection of the best alternative, (6) Application design, (7) Implementation; and (8) Testing. From these service activities, it was obtained as the result of an increase in the knowledge and understanding of the law of the community service participants regarding the control and handling of forest and land fires. This activity is carried out by evaluating the service participants by asking questions related to the service material that has been carried out. From an economic point of view, this activity is useful for communities around the forest so that they can enjoy the forest products they manage in the hope that there will be a stable economic increase and create jobs for future generations.